Determinants of Successful Treatment among New Tuberculosis Patients in Brebes Regency - Silvi Yanti; Lukman Fauzi (Journal of Health Education, 2023)
Background: Brebes Regency was ranked first with the highest TB incidence in Central Java in 2020. In 2021 the trend of TB incidence increased and the trend of Success Rate decreased from the previous two years. The study aims to determine the determinants of successful treatment among new TB patients in Brebes Regency. Method: The study design used was cross-sectional with the subject of new drug-sensitive TB patients in SITB from January 2020 to June 2022. A sample of 565 respondents was taken by simple random sampling. Data were analyzed univariately and bivariately with chi-square and Fisher's tests as well as multivariably using logistic regression test. Results: Among 565 new TB patients included in this study, 65,1% had successful TB treatment outcomes. In multivariable logistic regression analysis, the categorical variable of pulmonary TB patients (AdjOR: 0,27; 95% CI: 0,08-0,85; p=0,03), ratio of doctors (Q2) (AdjOR: 0,39; 95% CI: 1,18-0,87; p=0,02), microscopic test status at diagnosis (AdjOR: 2,09; 95% CI: 1,08-4,06; p=0,28 ), duration of treatment Q1 (AdjOR: 9,40; 95% CI: 4,27-20,69; p<0,001), Q2 (AdjOR: 0,08; 95% CI: 0,01-0,43; p<0,001), Q3 (AdjOR: 0,05; 95% CI: 0,01-0,30; p<0,001), and negative smear microscopic test results at month 2 after initiation of treatment (AdjOR: 9,80; 95% CI: 2,10-45,57; p<0,001) has a significant relationship to the successful TB treatment. Conclusion: Category of pulmonary TB, ratio of doctors 4,4-8,8 per 100,000 population, microscopy test status at diagnosis, length of treatment less than 7 months 11 days-12 months, and negative smear microscopic test results at the end of the 2nd month after the start treatment were determinants of successful treatment among new TB patients in Brebes Regency.